Development Law in the Context of Legal Theory and Philosophy: Challenges and Opportunities Toward Social Justice - Karina, Ica (Inovasi Pratama Internasional. Ltd, 2025)
This research project is an in-depth analysis of legal theory and philosophy in the context of the concept of development law. An understanding of how law functions as an instrument of social justice is crucial to this analysis. This research employs the literature study method to collect, distill, and interpret a range of academic sources pertaining to development law, social justice theory, and philosophical approaches that inform our understanding of justice in development. From a theoretical standpoint, this study draws upon relevant theories that emphasize equality of opportunity and resource distribution as a prerequisite for social justice. These theories are useful in emphasizing the importance of legislation that is capable of guaranteeing equal access and fair distribution. Furthermore, progressive legal theory and responsive legal thinking are investigated to ascertain how development law can serve as a dynamic instrument of change in alignment with social, cultural, and economic transformations. The findings of this research are anticipated to offer insight into how development law is not merely a collection of regulations but also an active instrument in fostering a more just and inclusive society. By incorporating aspects of social justice into development law, the prospect of realizing sustainable and balanced development is enhanced.